Enabling Horizontal Collaboration Through Continuous Relational Learning - Saenz, Maria Jesus; Ubaghs, Eduardo; Cuevas, Alejandra Isabel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Now that supply chain operations are facing new challenges due to the necessity of reducing costs and CO2 emissions, companies are increasingly leveraging cooperation from companies from other supply chains as a source of competitive advantage. Horizontal Collaboration has been proved an efficient tool for cutting logistic costs up to 49%. Zaragoza Logistics Center, member of the MIT-Scale Network, is publishing this book with the aim of building upon a framework of inter-organizational learning for horizontal collaboration on logistic operations. The outcome of this study is designed to help understand the relationship dynamics and managerial insights of horizontal collaboration for sustainable and profitable cooperation in freight distribution. The proposed collaborative practices are based on senior manager experiences from different industries: home appliances, automotive, retail, and food and beverage. Additionally, collaborative evidence from various successful pilot cases relevant to the distribution operations of the four industries are described, in order to illustrate the framework presented. This book fills a gap in the literature market and its insights encourages the readers to reflect on their own operational circumstances and challenges. Additionally, the book can be used as supplementary reading for master degree courses on supply chain collaboration, as well as courses in executive management.
1. Introduction -- 2. Inter-organizational Learning and Collaboration -- 3. Vertical Collaboration and Horizontal Collaboration in Supply Chain -- 4. Model for Horizontal Collaboration Dynamics -- 5. Case Studies -- 6. Managerial Recommendations -- Annexes.
Keywords: Production management; Engineering economics; Engineering economy; Industrial organization; Operations Management; Engineering Economics, Organization, Logistics, Marketing; Industrial Organization